1-Dimensional modelling of in-situ desulphurization performance of a 550 MWe ultra-supercritical CFB boiler. (15th April 2021) - Ke, Xiwei; Li, Dongfang; Li, Yiran; Jiang, Ling; Cai, Runxia; Lyu, Junfu; Yang, Hairui; Zhang, Man; Jeon, Chung-Hwan
Graphical abstract: A 1-dimensional CFB boiler model has been developed to simulate the mass balance and SO2 emission of the world first 550 MWe ultra-supercritical circulating fluidized bed boiler. Highlights: A 1-dimensional CFB boiler model has been developed. Mass balance and SO2 emission of the world first USC CFB boiler were simulated. The modelling results agree well with the field test data. Improving cyclone efficiency can improve in-situ desulphurization performance. Properly reducing limestone size can obtain higher desulphurization efficiency. Abstract: In the present work, the in-situ desulphurization performance of the world first 550 MWe ultra-supercritical (USC) circulating fluidized bed (CFB) boiler was investigated mainly through simulation method. A pseudo steady-state 1-dimensional CFB model has been developed that integrates and simultaneously predicts the particle balance, combustion, lime sulphation and some other aspects. The specially designed integrated recycle heat exchanger (INTREX) and bottom ash self-circulation system of this boiler are also considered. The predicted median diameters of fly ash, bottom ash and circulating ash are 16 μm, 238 μm and 142 μm, respectively, which agree well with the field test data. Both test and modelling results reveal that the when the fine limestone with a median diameter of 50 μm is applied, the in-situ desulphurization efficiency can reach up to 95% and the final SO2 emission is only around 20 ppm, while no any back-end FGD system is applied. A sensitivity analysis is carried out using the model to examine the effects of cyclone efficiency and limestone particle size on the in-situ desulphurization performance. It indicates that by improving the cyclone efficiency, the SO2 emission in the outlet of furnace significantly decreases. Besides, appropriately reducing the limestone size can obtain higher desulphurization efficiency. The model presented in this paper can be used to further study the operation characteristics of USC CFB boilers, also including in-situ desulphurization, which is important for accurate prediction and cost-effective control of SO2 emission.